English Course Handouts Using Text-Based Language Teaching for Students at Budidaya Tanamanan Perkebunan Politeknik Pertanian Negeri Payakumbuh - Hudia Hudia (International Journal of Educational Dynamics, 2019)
This study is entitled English Course Handouts Using Text-Based Language Teaching for Students at Budidaya Tanamanan Perkebunan Politeknik Pertanian Negeri Payakumbuh with Research and Development type. The subjects of this study were first semester students in the Department of Plantation Plant Cultivation, two lecturers of English Language courses, and two chairmen of Study Programs in the departmental environment. The instruments used were questionnaires, interview guides, and product validation sheets. The results of the study indicated that the current English language lecture material is General English which was not in accordance with the needs of students learning the language. Thus, it was necessary to develop English language material that can help students achieve learning targets. Text-based language teaching was used as a basis for learning because students need reading skills in English references to support their academic abilities. Other skills can be trained through activities that come from reading material in each handout. The products produced from this study are categorized as "valid" after being validated by experts with a score of 78.48 with a scale of 100. Student perceptions of handouts that are tested in a limited manner were interesting, easy to understand, and able to help them understand the lecture material given by the lecturer.